OVERVIEW OF ISLAMIC FAMILY FINANCIAL MANAGEMENT PLANNING: A PERSPECTIVE OF THE QUR'AN AND HADITH - Lifia, Lifia Lifia; Wahyuni, Nanik; Meldona, Meldona (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This review investigates the planning of Islamic family financial management by focusing on the perspective of the Qur'an and Hadith as the main sources of guidance. Involving an in-depth analysis of Islamic teachings, this study limits its scope to aspects of financial planning that include financial goal setting, management of expenditures, sound investment, and financial protection. By focusing on Muslim families, this review explains the principles of Islamic ethics and morality that form the foundation of family financial planning . Special aspects, such as debt management, separation of property and responsibilities, and their effe ct on family welfare, are central points in the discussion. The results of this review are expected to provide a deep insight into how important it is to integrate Islamic values in family financial planning to achieve financial sustainability and holistic well-being